PENILAIAN AUTENTIK DALAM PEMBELAJARAN TEMATIK DI SEKOLAH DASAR NEGERI KECAMATAN SUNGAI AMBAWANG - Pertiwi, Pertiwi; Marzuki, Marzuki; Sabri, Tahmid (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research was conducted based on the question of how authentic assessment implemented in thematic learning for public primary schools. It was aimed at describing the knowledge of teachers and principals about the implementation of authentic assessment in thematic learning at public primary schools. This research was a qualitative descriptive one with its subject of: teachers, students, and principals.  The data collection techniques used were interviews, observation, and documentation studies. The data were analyzed by reduction, presentation, and conclusion, preceded by the technique of triangulation data validity checking. The results of the research: 1) the teachers and principals comprehended authentic assessment in thematic learning; 2) the teachers performed authentic assessment in thematic learning by focusing on attitude competency, knowledge, and skill through integrated assessment. Assessment on the students? attitude was done through observation techniques, self-assessment, and peer assessment. The knowledge assessment was done through written test and assignments, while the skill assessment was performed through performance assessment techniques and portfolio assessment.Key words : authentical assessment, thematics learning